PERAN MANAJERIAL KEPALA SEKOLAH DALAM MUTU PEMBELAJARAN DI SD NEGERI TONJONG 01 KECAMATAN TONJONG KABUPATEN BREES - PURWANTI, SRI; MIYONO, NOOR; WURYANDINI, ENDANG (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
This study aims to analyze the managerial role of the principal in the quality of learning at SD Negeri Tonjong 01, Tonjong District, Brebes Regency. This study uses a qualitative approach method. The subjects of the study were the principal and teachers of SD Negeri Tonjong 01, Tonjong District, Brebes Regency. The data collection method used interviews, observation, and documentation. The data analysis technique used qualitative data analysis from Miles and Huberman. The results of this study explain the managerial role of the principal, namely the role in planning the quality of learning at SD Negeri Tonjong 01, namely the principal makes a comfortable school environment plan, fosters and assists in the preparation of learning tools, and prepares teacher competency development programs. The role in organizing includes: forming a school environment management team, forming a learning tool development team, and forming a learning community. The role in implementation includes: the principal is responsible for creating a comfortable and conducive school environment, both physically and psychologically, and managing the school ecosystem to be harmonious. Implementation of learning, class management, assessment The role in supervision includes supervising the school environment, supervising teaching and learning activities (KBM), and supervising the sustainability of the learning community. ABSTRAKPenelitian ini bertujuan untuk menganalisis peran manajerial kepala sekolah dalam mutu pembelajaran di SD Negeri Tonjong 01 Kecamatan Tonjong Kabupaten Brebes. Penelitian ini menggunakan metode pendekatan kualitatif. Subjek penelitiannya adalah kepala sekolah dan guru SD Negeri Tonjong 01 Kecamatan Tonjong Kabupaten Brebes. Metode pengumpulan data menggunakan wawancara, obeservasi, dan dokumentasi. Teknik analisis data menggunakan analisis data kualitatif dari Miles dan Huberman Hasil penelitian ini menjelaskan peran manajerial kepala sekolah yaitu peran dalam perencanaan mutu pembelajaran di SD Negeri Tonjong 01 yaitu kepala sekolah membuat perencanaan lingkungan sekolah yang nyaman, membina dan mendampingi penyusunan perangkat pembelajaran, dan menyusun program pengembangan kompetensi guru. Peran dalam pengorganisasian meliputi: membentuk Tim pengelola lingkungan sekolah, membentuk tim pengembang perangkat pembelajaran, dan membentuk komunitas belajar. Peran dalam pelaksanaan meliputi: kepala sekolah bertanggung jawab menciptakan lingkungan sekolah yang nyaman dan kondusif, baik secara fisik maupun psikologis, serta mengelola ekosistem sekolah agar harmonis. Pelaksanaan pembelajaran, pengelolaan kelas, penilaian Peran dalam pengawasan meliputi pengawaan lingkungan sekolah, pengawasan kegiatan belajar mengajar (KBM), dan pengawasan keberlanjutan komunitas belajar.